Premature ovarian insufficiency - to treat or not to treat? - O. S. Zahorodnia; I. B. Ventskivska; A. V. Kazak (Publishing House TRILIST, 2019)
Premature ovarian insufficiency (POI) is a rare but very damaging lifestyle condition that occurs at 1-1.5 of women and means termination of menstrual function up to 40 years old. POI impact on women's wellbeing includes lipid metabolism dysregulation, haemostasis regulation changes, both leading to heart diseases risk increasing, psychological problems, based on early reproductive function termination and anxiety because possible sexual dysfunction, manifestation of pelvic floor disorders. Patients with POI have symptoms, similar to women in menopause, namely vegetative nerve system disorders (hot flashes, night sweats, and emotional lability), insomnia and sexual dysfunction due to vaginal dryness, dyspareunia, and libido loss. It is believed, that estrogen and progesterone deficiency is a leading reason of these complains, but in the same time the role of testosterone decreasing concentration is discussed. Speaking accurately, therapy with exogenous estrogens for women with POI is really replacement, while for patients with normal age menopause it is rather therapy of extension. Nevertheless, only 52% patients with POI have discussed it with their doctors. The article deals with question hormone replacement therapy rationality from the point of view of most popular menopause disorders. Special trials for some of them are published, as for bone mineral density and sexual disorders, treatment for other is possible only by extrapolation from general cohort of menopausal women. For each position questions of effectiveness and safety is discussed. Different ways of estrogen administration are considered, as well as progestin variations. A special attention is paid to possibility of reproductive function restoration in patients with POI. Non-hormonal methods of menopause symptoms correction also discussed - from life style modification to drug administration.